2020
DOI: 10.1021/acs.jpca.0c08965
|View full text |Cite
|
Sign up to set email alerts
|

Visible-light-Induced Reaction of an Ozone–Trimethylamine Complex Studied by Matrix-Isolation IR and Visible Absorption Spectroscopies

Abstract: A visible-light-induced reaction of an O 3 −trimethylamine (TMA) complex isolated in low-temperature noble-gas matrices is investigated by infrared (IR) and visible absorption spectroscopies using the DFT calculation. The complex isolated in a Ne matrix yields trimethylamine-N-oxide (TMAO) upon irradiation (λ ≥ 800 nm) by dissociation of O 3 . When the wavelength of radiation is changed to λ = 455 nm, two stable conformers of dimethylaminomethanol (DMAM) are recognized besides TMAO. In an Ar matrix, DMAM and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 25 publications
3
10
0
Order By: Relevance
“…In this study, the types of photoproducts derived were not dependent on the wavelength of the light source. Kamata et al [53] and Kon et al [54] reported the switching of photoreaction channels at visible wavelengths. It is still not clear how and why such differences arise, which presents another issue to be solved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the types of photoproducts derived were not dependent on the wavelength of the light source. Kamata et al [53] and Kon et al [54] reported the switching of photoreaction channels at visible wavelengths. It is still not clear how and why such differences arise, which presents another issue to be solved.…”
Section: Discussionmentioning
confidence: 99%
“…length of the light source. Kamata et al [53] and Kon et al [54] report photoreaction channels at visible wavelengths. It is still not clear how ferences arise, which presents another issue to be solved.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies on the UV-induced reactions of O 3 have been reported to date. , In contrast, the visible-light-induced reactions of O 3 that produce O­( 3 P) are not important in atmospheric chemistry because the cross sections of the Chappuis and Wulf bands appearing at ∼600 nm and in the near-infrared region are much lower than the Hartley band at ∼250 nm. , In addition, O­( 3 P) produced via visible photoreaction of O 3 has a negligible effect on the various reactions observed in the troposphere. However, it has often been reported that the visible-light absorption of O 3 is enhanced by forming a molecular complex isolated in a low-temperature noble-gas matrix. For example, O 3 -ferrocene isolated in an Ar matrix exhibits two bands at 361 and 765 nm, whereas O 3 -dimethylsulfide (DMS) in a Ne matrix has two bands appearing at 480 and 600 nm, and two bands are observed for O 3 -dimethylamine (DMA) in an Ar matrix at 430 and 613 nm . In addition, the bands observed at 465 and 645 nm in the visible spectrum of O 3 -trimethylamine (TMA) in an Ar matrix are shifted to 455 and 635 nm, respectively in a Ne matrix .…”
Section: Introductionmentioning
confidence: 99%
“…However, it has often been reported that the visible-light absorption of O 3 is enhanced by forming a molecular complex isolated in a low-temperature noble-gas matrix. For example, O 3 -ferrocene isolated in an Ar matrix exhibits two bands at 361 and 765 nm, whereas O 3 -dimethylsulfide (DMS) in a Ne matrix has two bands appearing at 480 and 600 nm, and two bands are observed for O 3 -dimethylamine (DMA) in an Ar matrix at 430 and 613 nm . In addition, the bands observed at 465 and 645 nm in the visible spectrum of O 3 -trimethylamine (TMA) in an Ar matrix are shifted to 455 and 635 nm, respectively in a Ne matrix . These studies suggest that the absorption wavelengths of O 3 are affected by the type of paired molecule and the surrounding medium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation